Respostas
respondido por:
3
a)
3x + 4 (1 + x) + 2 = 5x - x - 6
3x + 4 + 4x + 2 = 4x - 6
7x + 6 = 4x - 6
7x - 4x = - 6 - 6
3x = - 12
x = -12/3
x = - 4
b)
2x - x = 6(x - 2)
3 5
2x - x = 6x - 12
3 5
mmc de 3,5 = 15
5.2x - 3.x = 15. (6x - 12)
15 15
10x - 3x = 90x - 180
7x = 90x - 180
180 = 90x - 7x
180 = 83x
83x = 180
x = 180
83
********************
3x + 4 (1 + x) + 2 = 5x - x - 6
3x + 4 + 4x + 2 = 4x - 6
7x + 6 = 4x - 6
7x - 4x = - 6 - 6
3x = - 12
x = -12/3
x = - 4
b)
2x - x = 6(x - 2)
3 5
2x - x = 6x - 12
3 5
mmc de 3,5 = 15
5.2x - 3.x = 15. (6x - 12)
15 15
10x - 3x = 90x - 180
7x = 90x - 180
180 = 90x - 7x
180 = 83x
83x = 180
x = 180
83
********************
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás